The Characteristics Physicochemical of Instant Drink From Groove Leaves (Suaeda maritima) Using Maltodextrin Of Taro Tubers - Dedin Finatsiyatull Rosida; Ratna Yulistiani; Ratna Nur Fitria Mabbrury (Future Science, 2022)
Leaf groove is rich in antioxidants so they can be beneficial for health. Leaf grooves have a weakness which is a salty taste, so to reduce the salty taste, a soaking process is carried out and made into food products that are easier to consume. The instant drink is one product that is easy to implement for the public. The process of making instant drinks needs to be added with fillers. The filler used in this study was maltodextrin from taro tubers. In general, maltodextrin is made from cassava. The function of maltodextrin can increase volume, accelerate drying, increase solubility, and can coat flavor components. This study aims to determine the effect of the ratio of the extract of the groove leaves and the concentration of maltodextrin from the taro tubers on the physicochemical and organoleptic characteristics of the instant drink. This study used a factorial completely randomized design (CRD) with two factors. The first factor was the ratio of groove leaf extract and water (1:1, 1:2, and 1:3). The second factor was the concentration of taro tuber maltodextrin (5%, 10%, and 15%). The data obtained were analyzed using ANOVA, if there was a significant difference, it was continued with Duncan's Test (DMRT). The results showed that the treatment of dilution of groove leaf extract (1:1) with the addition of 15% maltodextrin was the best treatment that produced a grooved instant drink with a water content of 3.87%, ash 3.75%, salt 0.60%, solubility 91.947%, and the organoleptic Hedonic Scale Scoring test includes color 5.88 (like very much), taste 4.54 (likes) and aroma 4.8 (likes).